Faktor Interaksi Sosial pada Anak Autis di Pusat Layanan Autis - Wilda Sinaga; Nur Insani; Reta Renylda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the factors influencing social interaction in autistic children, particularly related to parental acceptance and roles. The method used in this research is cross-sectional. The results of this study indicate that as many as 56.7% of autistic children have good social interactions, 56.7% of parents' acceptance is not good, and 63.3% of parents' roles are classified as good. The results of statistical tests showed that there was a significant relationship between parental acceptance (p-value 0.010; OR 10.083; 95% CI 1.658-61.33) and parental roles (p-value 0.023; OR 7.467; 95% CI 1.4-39.836). with the social interactions of children with autism. In conclusion, the social interaction of autistic children can be increased by the parents' acceptance towards their children and the parenting role of parents towards their children. Keywords: Autism, Social Interaction, Parental Acceptance, Parental Role